Article history: Received March 29, 2024 Revised August 20, 2024 Accepted Nov 18, 2024 Keywords: Learning Media, Puzzles, Plant Reproduction Implementasi Pengembangan Media Puzzle Kreatif Pada Materi Perkembangbiakan Tumbuhan Pelajaran IPAS Di Kelas 4 - Anggraeni, Dita Wahyu; Nuruddin, Muhammad; Asmarani, Ratih (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The aim of this research is to develop puzzle media for IPAS plant reproduction. This research uses the ADDIE model which has 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. The aim of this research is to determine the development of puzzle media and the feasibility of the puzzle media. This research uses a questionnaire to test the suitability of the media through media expert validation and material expert validation. The media expert validation results show that the results are categorized as